Performance of waste cooking oil esterification for biodiesel production using various catalysts - Herman, Indah Thuraya; Khairuddin, Md Isa; Naimah, Ibrahim; Saiful Azhar, Saad; Tuan Amran, Abdullah; Mohd Aizudin, Abd Aziz; Muhammad Auni, Hairunnaja (Universiti Putra Malaysia Press, 2024)
In this study, waste cooking oil (WCO) with high free fatty acid (FFA) content was esterified to produce biodiesel, and the catalysts’ performance was investigated. Two deep eutectic solvents (DESs) were employed as the liquid catalysts (K2CO3-Gly and KOH-Gly), while the solid heterogeneous catalysts used were spent bleaching earth (SBE), KCC-1, and Na/KCC-1. DESs were prepared by mixing at reaction temperature and time of 80°C and 120 min, respectively. The American Standard Testing Method (ASTM) D974 determined the acid value. The catalysts were first screened for their catalytic activity in WCO esterification. The parameters investigated in this study were oil-to-methanol molar ratio, catalyst loading, reaction time, and temperature. The highest conversion (94.7%) was obtained using Na/KCC-1. The performance of solid and liquid catalysts was evaluated using KOH-Gly and SBE for the reduction of FFA in WCO under different conditions of oil-to-methanol molar ratio (1:6–1:10), catalysts loading (0.2–2.0 g), reaction time (30–60 min), and temperature (40–100°C). The highest reduction of FFA in the esterification process for KOH-Gly and SBE as catalysts was 97.74% and 84.2%, respectively. Transesterification of the esterified oil shows a promising result (97%), and the process can potentially be scaled up. The GC-MS result shows that the produced oil has the highest percentage of hexadecanoic acid and methyl ester.